Inner Cover and Content Strategic Review for Southern Africa (The Strategic Review for Southern Africa, 2020)
The Strategic Review for Southern Africa is an accredited open-access journal listed in the IBSS index and the DHET list. It has since 1978 been a platform for strategic and political analyses of themes and socio-political developments that impact on or provide lessons for Southern Africa. As a multi-disciplinary, interdisciplinary and transdisciplinary journal, the Strategic Review facilitates vigorous and enlightened debate among scholars, policy makers, practitioners, students and activists in order to contribute to the wider global discourse on changing strategic and political dynamics within and beyond nation states.The journal publishes two regular issues a year (May/June and November/December) with a possibility of one additional guest special issue per year as need justifies, subject to board approval. Issues are available mainly as an open access online platform licensed under creative commons. Printed copies can be ordered. All submissions are subject to double-blind peer review by at least two appropriately qualified reviewers.
Keywords: Southern Africa; scholars; policy makers; practitioners; nterdisciplinary and transdisciplinary journal; students and activists; political dynamics